Experimental study on the magnetic permeability of inclusion filled soft polymeric composite for soft-core transformer applications - Xiaocheng Hu (Elsevier, 2022)
The magnetic permeability of three kinds of inclusions (Carbonyl iron, Ferroferric oxide, NiFe-alloy) filled polymer (Polydimethylsiloxane) is investigated at room temperature by using a Buck circuit for the dynamic test and vibrating sample magnetometer (VSM) for the static test. Unlike the traditional measurement method using an impedance analyzer, the self-built circuit can generate a maximum test current of ampere amplitude over high frequencies to simulate the transformer's operation status. The present work considers the effects of inclusion content (from 0 VOL.% to 33 VOL.%) and testing frequencies(100 kHz-1MHz). The experimental results of permeability are compared with the theoretical predictions in the previous works. Three main conclusions can be drawn: First, the magnetic permeability increases with the inclusion addition; Second, as the testing frequency increases, the permeability of the composite material maintains constant, showing no evident dependence on the testing frequency; Third, type of magnetic inclusion will gently affect the permeability of the composite material. This work systematically investigated the permeability of polymer-based magnetic materials, and the results are helpful for the soft-core transformer application of magnetoactive elastomers.